Assessment of CD56 and CD14 by IHC in Placental tissues from women with miscarriage - Hamid, Zainab A.; Zangor, Jabbar R.; Bayati, Ali H.; Mohammed Ali, Saad H. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Among many possible causes, CD14, CD 56, were implicated in immune mechanisms and might be involved in pregnancy loss. However the role of these Immunological factors has not been clearly elucidated. Some authors have shown that women with reproductive failure (such as spontaneous miscarriage) have increased CD14, uNK cells numbers; where as other authors reported no difference or even reduced numbers.Objective: The aim of this study was to have an insight in a panel of the immunological factors shared in the placental microenvironment in an attempt to find a close relationships of these markers to the state of abortions.Methods: Immunohistochemistry technique assay was used to detect CD14 and CD56 in 40 women with spontaneous miscarriage and in 40 healthy deliveries in Baghdad/Iraq.Results: The CD56 protein detected as by IHC in 60.0% and 5.0% of miscarriage and healthy delivered women groups respectively which showed statistically Significant differences ( p